Bark thickness and fire regime - Pausas, Juli G. (Functional ecology, 2015)
Summary Bark is a vital and very visible part of woody plants, yet only recently has bark characteristics started to be considered as key traits structuring communities and biomes. Bark thickness is very variable among woody plants, and I hypothesize that fire is a key factor selecting for a thick bark, and thus, at the global scale, a significant proportion of the variability in bark thickness is explained by the variability in fire regimes. Previous research has focused on the importance of bark thickness mainly in surface‐fire regimes; here I generalize this idea and present a conceptual framework to explain how the different drivers that affect fire intensity have shaped bark thickness, in conjunction with other plant traits. I first review methods used to study bark thickness and then provide examples of bark thickness patterns from a wide range of ecosystems subject to different fire regimes (understorey fires, grass‐fuelled surface fires, grass‐fuelled crown fires and infrequent fires). There are some fire regimes that select for thick barks, while some only in the base of the trunk (e.g. understorey fires), others select for a thick bark on the whole plant (e.g. grass‐fuelled crown fires). There are also fire regimes in which allocating resources to a thick bark is not adaptive (e.g. woody‐fulled crown fires). Fire regime can explain a large proportion of the variability of bark thickness at the global scale, and thus, this trait varies across ecosystems in a predictable manner; however, the current paucity of data limits a fully accurate analysis. Lay Summary